2020
DOI: 10.1186/s13567-020-00757-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dendritic cells and follicular dendritic cells in the hepatic lymph nodes and liver of sheep experimentally infected with Fasciola hepatica

Abstract: Fasciola hepatica has been shown to have a high capacity for immunomodulation of the host response, making the development of protective vaccines extremely difficult. One of these immunomodulation mechanisms is the impairment of dendritic cells (DC) maturation and, therefore, suppression of antigenic presentation. The aim of this study was to evaluate the pathological changes as well as the characterization of two antigen presenting cells, DC (CD1b, CD83 and MHC-II positive) and follicular dendritic cells (FDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, Falcoń et al (80) found that DC stimulated with F. hepatica excretory-secretory products (ESP) primed CD4+ cells towards a T h 2/regulatory response, with increased production of IL-4, IL-5, IL-10 and TGF-b, and reduced IFN-g. Some of these changes have been observed in sheep, where infection with F. hepatica produced hyperplasia of the hepatic lymph nodes with increased numbers of DC at 18 dpi, but a significant decrease in the expression of their antigen presentation markers (CD83 and MHC-II) (85). Our results indicate an increased expression of both the CD83 and CD40 genes, which could indicate a difference between acute and chronic infections.…”
Section: Dendritic Cells and Their Interactions Are Affectedsupporting
confidence: 63%
“…Furthermore, Falcoń et al (80) found that DC stimulated with F. hepatica excretory-secretory products (ESP) primed CD4+ cells towards a T h 2/regulatory response, with increased production of IL-4, IL-5, IL-10 and TGF-b, and reduced IFN-g. Some of these changes have been observed in sheep, where infection with F. hepatica produced hyperplasia of the hepatic lymph nodes with increased numbers of DC at 18 dpi, but a significant decrease in the expression of their antigen presentation markers (CD83 and MHC-II) (85). Our results indicate an increased expression of both the CD83 and CD40 genes, which could indicate a difference between acute and chronic infections.…”
Section: Dendritic Cells and Their Interactions Are Affectedsupporting
confidence: 63%
“…This makes chronicity one of the consequences of the regulated milieu induced by the parasite, and the main obstacle in producing an effective vaccine [16,17]. The capacity of F. hepatica to downregulate the Th1 proinflammatory immune response and upregulate the Th2 anti-inflammatory immune response beginning at early stages of infection in sheep has been previously described [18][19][20][21][22]. This scenario implies the downregulation of IFN-γ expression and the upregulation of IL-4 expression, leading to the suppression of the Th1 pro-inflammatory immune response and promoting a Th2 non-protective immune response.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, F. hepatica cathepsin L1 (FhCL1), glutathione S-transferase (FhGST), and Kunitz-type molecule participate in the modulation of DCs, leading to the suppression of the adaptive immune responses, Th1, and/or Th17 ( 40 , 97 ). F. hepatica -infected sheep showed increased numbers of DCs in the hepatic lymph nodes but reduced expression of MHC class II and CD83, suggesting suppression of the antigen-presentation process in lymphocytes both in the early and late stages of infection ( 125 ).…”
Section: Immunomodulation Strategiesmentioning
confidence: 99%